Desarrollo de una aplicación web utilizando la metodología Feature Driven Development (FDD) para automatizar el control de inventario, en el Centro Cristiano Evangélico Camino a Damasco del Cantón Colta, parroquia Cajabamba - Llangari Guamán, David Wilfrido (2023)
This research addressed the problem of the need for a reliable and accurate application for inventory control and management in Centro Cristiano Camino de Damascus. This situation generated errors in decision-making, resulting in a loss of time and money that affected all areas of the company's activity, including community services.The study's general objective was to implement a web application for inventory control of the Evangelical Christian Center on the Road to Damascus, using the Feature Driven Development (FDD) methodology. The specific objectives included: •The investigation of the FDD methodology. •The development of the web application. •The evaluation of its usability using the ISO/IEC 25000 standard. The FDD methodology was selected as the primary approach for web application development due to its incremental and feature-oriented approach. It allowed the result to be divided into small functionalities developed independently and then integrated into the final application, providing a structured and organized framework.As a result of the research and application of the FDD methodology, it was possible to develop a practical web application for inventory control at the Evangelical Christian Center on the Road to Damascus. The application met the established requirements and functionalities, optimizing the inventory management process and minimizing errors in decision-making